Functional diversification of Flowering Locus T homologs in soybean: GmFT1a and GmFT2a/5a have opposite roles in controlling flowering and maturation. Issue 3 (9th November 2017) - Liu, Wei; Jiang, Bingjun; Ma, Liming; Zhang, Shouwei; Zhai, Hong; Xu, Xin; Hou, Wensheng; Xia, Zhengjun; Wu, Cunxiang; Sun, Shi; Wu, Tingting; Chen, Li; et al.
Summary: Soybean flowering and maturation are strictly regulated by photoperiod. Photoperiod‐sensitive soybean varieties can undergo flowering reversion when switched from short‐day (SD) to long‐day (LD) conditions, suggesting the presence of a 'floral‐inhibitor' under LD conditions. We combined gene expression profiling with a study of transgenic plants and confirmed that GmFT1a, soybean Flowering Locus T ( FT ) homolog, is a floral inhibitor. GmFT1a is expressed specifically in leaves, similar to the flowering‐promoting FT homologs GmFT2a/5a . However, in Zigongdongdou (ZGDD), a model variety for studying flowering reversion, GmFT1a expression was induced by LD but inhibited by SD conditions. This was unexpected, as it is the complete opposite of the expression of flowering promoters GmFT2a/5a . Moreover, the key soybean maturity gene E1 may up‐regulate GmFT1a expression. It is also notable that GmFT1a expression was conspicuously high in late‐flowering varieties. Transgenic overexpression of GmFT1a delayed flowering and maturation in soybean, confirming that GmFT1a functions as a flowering inhibitor. This discovery highlights the complex impacts of the functional diversification of the FT gene family in soybean, and implies that antagonism between flowering‐inhibiting and flowering‐promoting FT homologs in this highly photoperiod‐sensitive plant may specify vegetative vs reproductive development.